Septic shock caused by Elizabethkingia miricola in an elderly trauma patient: a case report and systematic literature review - Mao, Xiaoxiao; Feng, Xiao; Li, Chaoyang; Xu, Xiupeng; Zhao, Lin; Xu, Jia; Bi, Liqing; Yue, Zhen (Frontiers in Medicine, 2025)
ObjectiveElizabethkingia miricola is a rarely encountered pathogen in clinical settings, predominantly causing infections in immunocompromised individuals. To advance the understanding of E. miricola infection, we present a case of E. miricola infection and conduct a literature review.MethodsWe report a case of pulmonary infection caused by E. miricola in a 90-year-old trauma patient, marking the first documented instance of treatment with eravacycline. We also conducted a systematic review of the relevant literature. A comprehensive search was performed using the PubMed and Web of Science databases up to November 2024. A qualitative synthesis was conducted on all available case reports and case series related to E. miricola infections.ResultsA total of 63 cases from 21 studies were included in this systematic review. According to these case reports, infections caused by E. miricola most commonly occur in the lungs (34/63), bloodstream (6/63), and urinary tract (4/63). Risk factors for E. miricola infection include immunodeficiency, prolonged hospitalization in the intensive care unit (ICU), prolonged mechanical ventilation, and the use of broad-spectrum antibiotics. Notably, a considerable proportion of cases (17/63) are hospital-acquired.ConclusionElizabethkingia miricola represents a rare but highly lethal opportunistic pathogen. Early identification and treatment with sensitive antibiotics are required to improve the prognosis of patients. The present case and literature review provide options for the diagnosis and treatment of similar cases in the future and serve as a reference for preventing and controlling the occurrence and spread of nosocomial infections.Systematic review registrationhttps://pubmed.ncbi.nlm.nih.gov/, https://www.webofscience.com/wos/.